Severe floods in Jammu & Kashmir in August I973 - GHOSH , S. K.; VEERARAGHAVAN, K. (MAUSAM, 1975)
Occurrence of severe flood in Jammu & Kashmir in-August 1973 has been reported. The meteorolugical situations responsible for such a severe flood have been studied. It is shown that floods in Jammu & Kashmir can occur even in the absence of monsoon depressions and western disturbances but under the favourable Influence of (1) deep penetration of monsoon air Into the area and (11) high level trough-jet system.